Mitochondrial metabolism is rapidly re-activated in mature neutrophils to support stimulation-induced response - Lika, Jorgo; Votava, James A.; Datta, Rupsa; Mellado Fritz, Carlos A.; Kralovec, Aleksandr M.; Smith, Frances M.; Huttenlocher, Anna; Skala, Melissa C.; Fan, Jing (Frontiers in Immunology, 2025)
IntroductionNeutrophils are highly abundant innate immune cells that are constantly produced from myeloid progenitors in the bone marrow. Differentiated neutrophils can perform an arsenal of effector functions critical for host defense. This study aims to quantitatively understand neutrophil mitochondrial metabolism throughout differentiation and activation, and to elucidate the impact of mitochondrial metabolism on neutrophil functions.MethodsTo study metabolic remodeling throughout neutrophil differentiation, murine ER-Hoxb8 myeloid progenitor-derived neutrophils and human induced pluripotent stem cell-derived neutrophils were assessed as models. To study the metabolic remodeling upon neutrophil activation, differentiated ER-Hoxb8 neutrophils and primary human neutrophils were activated with various stimuli, including ionomycin, monosodium urate crystals, and phorbol 12-myristate 13-acetate. Characterization of cellular metabolism by isotopic tracing, extracellular flux analysis, metabolomics, and fluorescence-lifetime imaging microscopy revealed dynamic changes in mitochondrial metabolism.ResultsAs neutrophils mature, mitochondrial metabolism decreases drastically, energy production is offloaded from oxidative phosphorylation, and glucose oxidation through the TCA cycle is substantially reduced. Nonetheless, mature neutrophils retain the capacity for mitochondrial metabolism. Upon stimulation with certain stimuli, TCA cycle is rapidly activated. Mitochondrial pyruvate carrier inhibitors reduce this re-activation of the TCA cycle and inhibit the release of neutrophil extracellular traps. Treatment with these inhibitors also impacts neutrophil redox status, migration, and apoptosis without significantly changing overall bioenergetics.ConclusionsTogether, these results demonstrate that mitochondrial metabolism is dynamically remodeled and plays a significant role in neutrophils. Furthermore, these findings point to the therapeutic potential of mitochondrial pyruvate carrier inhibitors in a range of conditions where dysregulated neutrophil response drives inflammation and contributes to pathology.